(untitled) (The Research of Medical Science Review, 2024)
Mosquitoes are the small flies belong to class insecta and order diptera. These are the life threatening organisms and kill almost one million people in a year by transmitting severe diseases, as it is the vector of many diseases. The life cycle of mosquito is divided in to four different stages which include egg, larva, pupa and adult. The larval stage of mosquito feeding is the most active stage. In this study the lead oxides nanoparticles were synthesized and used as insecticide on the mosquito larvae. The nanoparticles (NP) were prepared by adding lead acetate and NaOH. The solutions of lead acetate and NaOH were mixed thoroughly. The color of solution changed into cloudy. The mixture of solutions was heated till the color of solution turned into peach, then in orange color and finally turned into red. The water evaporated completely and ,the nanoparticles were washed several times to reduce pH until it reached around neutral. They were characterized by the scanning electron microscope. Five different dilutions of lead oxide nanoparticles were used on mosquito larvae which were arranged in five beakers. In each beaker 20 larvae were added. The concentrations of lead oxide NP were set of 2mg/L, 4mg/L, 6mg/L, and 8mg/L and10mg/L. The experiment was observed after 24 hours, 48hours and 72hours. It was observed that after 24 hours at the concentration of 2mg/L, 4mg/L and 6mg/L of PbO3 -NPs about 5% mosquitoes died. At higher concentration of PbO3-NPs e.g. 8mg/L about 20% and at 10mg/L 30% mosquito larvae death was observed. After 48 hours the toxicity against larvae was increased with increase in concentration. At highest concentration of 10mg/L about 60% larval death was observed. After 72 hours the toxicity against mosquito larvae was higher than 1 and 2 days . At concentration of 6mg/L, 8mg/L and 10mg/L about 40%, 70% and 95% larval death was recorded.